Hubungan Gula Darah Dan Indeks Massa Tubuh (IMT) Terhadap Kejadian Gangguan Siklus Menstruasi Pada Mahasiswi: Hubungan Gula Darah Dan Indeks Massa Tubuh (IMT) Terhadap Kejadian Gangguan Siklus Menstruasi Pada Mahasiswi - Nurpratiwi, Yulidian; Sartika, Mila; Setiawati, Yuyun; Masnan, Trismayani (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Increased blood sugar and BMI are factors that can affect the incidence of menstrual cycle disorders. The purpose of this study was to determine the relationship between blood sugar levels and BMI on the incidence of menstrual cycle disorders in nursing students of FIKes-UMS. This research design is quantitative analytic with cross sectional design. The population in this study were all nursing students of UMS as many as 66 respondents, with total sampling technique. Data collection with a questionnaire contains the value of Timed Blood Glucose and BMI. Chi-Square statistical analysis test obtained p-value <0.05 which means there is a significant relationship between blood sugar levels and BMI on the incidence of menstrual cycle disorders. The conclusion is that there is a relationship between blood sugar and BMI on the incidence of menstrual cycle disorders in female FIKes-UMS students. Suggestions are expected that research can be developed again for further researchers by adding variables, the number of respondents and research methods.